Some critical factors for photocatalysis on self-organized TiO2 nanotubes - Liu, Ning; Paramasivam, Indhumati; Yang, Mingjun; Schmuki, Patrik (Journal of Solid State Electrochemistry, 2012)
In the present work, different intrinsic and extrinsic parameters are investigated that affect the photocatalytic activity of self-organized TiO2 nanotube layers. Particularly, the influence of annealing temperature and annealing atmosphere, the influence of different gas purging in the electrolyte, and the effect of applied voltage on the photocatalytic degradation rates of acid orange (AO7) are discussed. We find that the effect of the reducing gas atmosphere dominates over the anatase/rutile ratio in activating the nanotube layers. Moreover, we show that the effect of different gas purging (Ar and O2) of the electrolyte affects the reaction rate twofold: (1) by providing electron acceptor states and also by (2) a different change in the red–ox potential, i.e., the band bending in TiO2. By an external anodic voltage, the reaction rates can be increased drastically due to increased band bending. Nevertheless, the magnitude of the effect is also affected by the presence or absence of O2 in the electrolyte.
EAM Import::2019-03-13